Interferometric Detection of Single Gold Nanoparticles Calibrated against TEM Size Distributions. Issue 29 (30th March 2015) - Zhang, Lixue; Christensen, Sune M.; Bendix, Poul Martin; Bhatia, Vikram Kjøller; Loft, Steffen; Stamou, Dimitrios
<x xml:space="preserve">Abstract</x> Single nanoparticle analysis: An interferometric optical approach calibrates sizes of gold nanoparticles (AuNPs) from the interference intensities by calibrating their interferometric signals against the corresponding transmission electron microscopy measurements. This method is used to investigate whether size affects the diffusion behavior of AuNPs conjugated to supported lipid bilayer membranes and to multiplex the simultaneous detection of three different AuNP labels.